Frecuencia de cultivos de Pseudomonas aeruginosa y Klebsiella pneumoniae productoras de metalobetalactamasas de origen hospitalario - Polo Tacanga, Rosa Luz (2018)
The objective of this work was to determine the frequency of crops of Pseudomonas aeruginosa and Klebsiella pneumoniae producers of metallobetalactamases of hospital origin, for the study 30 crops of both species of microorganisms were analyzed. For the detection of metallobetalactamases, the Kirby-Bauer preliminary disc diffusion method was used and the positive double-disc synergy confirmatory test was obtained. The frequency of metalobetalactamase producing crops 13.3% and 3.3% for Pseudomonas aeruginosa and Klebsiella pneumoniae respectively. Not Finding significance in the production of metallobetalactamases between the same species of Pseudomonas aeruginosa and Klebsiella pneumoniae.